Prognostic significance of ING3 expression in patients with cancer: A systematic review and meta-analysis - Li, Zehan; Xu, Shengchao; Chen, Lin; Huang, Shuqi; Kuerban, Xieyida; Li, Tianyu (Frontiers in Oncology, 2023)
Abstract Background It has been reported that ING3 inhibits the progression of various cancers, however, some studies have shown that it promotes the development of prostate cancer. The purpose of this study was to investigate if ING3 expression is associated with the prognosis of patients with cancer. Materials and methods Pubmed, the Cochrane Database, Embase, Medline, ScienceDirect, Scopus and Web of Science were searched up to September 2022. Hazard ratio (HR)/odds ratio (OR), as well as their 95% confidence interval (95% CI), was calculated using Stata 17 software. We used Newcastle-Ottawa Scale (NOS) to assess the risk of bias. Result Seven studies including 2371 patients with 5 types of cancers were included. The results showed that high expression of ING3 was negatively associated with a more advanced TNM stage (III-IV vs. I-II) (OR=0.61, 95% CI: 0.43-0.86), lymph node metastasis (OR=0.67, 95% CI: 0.49-0.90) and disease-free survival (HR=0.63, 95% CI: 0.37-0.88) . However, ING3 expression was not associated with overall survival (HR=0.77, 95% CI: 0.41-1.12), tumor size (OR=0.67, 95% CI: 0.33-1.37), tumor differentiation (OR=0.86, 95% CI: 0.36-2.09) and gender (OR=1.14, 95% CI: 0.78-1.66). Conclusion This study showed that the expression of ING3 was associated with better prognosis, suggesting that ING3 may be a potential biomarker for cancer prognosis.